Genetic insights of carotenoids, quality protein, and grain yield in biofortified tropical maize - Bashir Omolaran Bello (Indonesian Journal of Agricultural Research, 2026)
Biofortified Provitamin A Quality Protein Maize (PVA-QPM) varieties enhance nutritional quality, addressing malnutrition in maize-based diets and strengthening food security in West and Central Africa. This study assessed genetic relationships among grain yield, tryptophan, and carotenoids in ten early-maturing PVA-QPM inbreds and two commercial checks evaluated under rainfed conditions in Nigeria across 2022 and 2023. Data were analyzed for variance components, genetic parameters, and heritability. Commercial checks outperformed inbreds in grain yield, with TZEIORQ 47 producing 5.99 t ha⁻¹, only 6.6% lower than the highest-yielding check, Oba Super 4. In contrast, inbreds expressed higher tryptophan, with TZEIORQ 13 recording a 49% advantage over checks. Substantial genetic variability was observed across traits, with high heritability for grain yield and carotenoids and moderate heritability for tryptophan. Correlation analysis revealed that grain yield was positively associated with total carotenoids (r = 0.62, p < 0.05) but negatively correlated with tryptophan (r = –0.47, p < 0.05), highlighting a trade-off between yield potential and protein quality. Carotenoids and tryptophan were not significantly correlated, indicating that they are inherited independently. These results provide critical insights for simultaneous improvement of yield and nutritional traits, supporting targeted breeding strategies for biofortified maize in sub-Saharan Africa.